THE ROLE OF MILITARY IN THE SOGDIAN SOCIETY IN THE EARLY MIDDLE AGES (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
Due to its strategic location, Central Asia has historically been a region of significant military activity, with numerous military campaigns aimed at controlling these territories. In particular, the Sogdian state was under the constant influence of military operations for several centuries. This article discusses the role of the Sogdian Confederation's military in society, as well as the descriptions of military titles, based on the research of leading Sogdian scholars.